Characterisation Of Polyhydroxyalkanoate Synthesis - Mok, Pei Shze (2019)
Polyhydroxyalkanoate (PHA) is a biodegradable and renewable thermoplastic that has potential to replace synthetic petroleum-based plastic due to their similar properties. Azotobacter vinelandii, a Gram-negative soil bacterium, is one of the microbes that can produce PHA. Many studies have been carried out to increase the production or value of PHA. In this study, a wild type strain, A. vinelandii ATCC 12837, and a deletion mutant of A. vinelandii that without or lacks the S-layer, designated as ΔAvin_16040, were used to produce PHA. The PHA accumulation was evaluated under different parameters and compared with wild-type strain. Around 3-fold higher amount of PHA was obtainable by the mutant strain compared to the wild type strain and the absence of the S-layer surrounding the cell was believed to played important role on higher PHA production. Optimisation on PHA production by the mutant strain had shown increment of 6 % and 39.5 % for cell dry weight and PHA concentration, respectively. The properties of poly(3-hydroxybutyrate), [P(3HB)] between two A. vinelandii strains were similar in terms of molecular weight, thermal and tensile properties. Besides, this bacterium is known to produce PHA containing 3-hydroxybutyrate (3HB) or mixture of 3HB and 3-hydroxyvalerate (3HV). Interestingly, in this study, 4-hydroxybutyrate (4HB) monomer was discovered to be incorporated for formation of poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)] by both the wild type and mutant strains when structurally-related carbon source was provided.